Eco-epidemiology of rodent-associated trombiculid mites and infection with Orientia spp. in Southern Chile - Silva, María; Pérez, Caricia; Martínez, Constanza; Pérez, Ruth; Vial Cox, María Cecilia; Stekolnikov, Alexandr; Abarca, Katia; Thomas Weitzel; Weitzel, Thomas; Acosta, Gerardo (PLOS Neglected Tropical Diseases, 2023)
Background: Scrub typhus is a potentially severe infection caused by bacteria of the genus Orientia, endemic in Asia-Pacific and recently discovered in southern Chile. The presented study aimed to determine the prevalence and species richness of rodent-associated trombiculid mites and their infection with Orientia spp. in different areas of two regions in southern Chile. Methodology/principal findings: During summer 2020, trombiculid mites were collected from rodents captured in three areas in southern Chile known to be endemic for scrub typhus (Cochamó and Chiloé Island in the Los Lagos Region and Tortel in the Aysén Region). A total of 132 rodents belonging to five species were captured using Sherman-like traps; 89.4% were infested with trombiculids. Mite specimens were morphologically identified and subsequently tested by Orientia-specific qPCR. Six mite species were identified. Among chigger-infested rodents, 33.9% carried Orientia-positive mites; this rate was higher in Tortel (63.8%) than in Cochamó (45.0%) and Chiloé Island (2.0%). The analysis of individual mites (n = 901) revealed that 31.2% of Herpetacarus antarctica samples (n = 202) were positive for Orientia DNA; the prevalence was 7.0% in Paratrombicula neuquenensis (n = 213), 6.9% in Herpetacarus eloisae (n = 144), 3.6% in Argentinacarus expansus (n = 55), and 0% in Paratrombicula goffi (n = 110) and Quadraseta chiloensis (n = 177). The southernmost site (Tortel) showed the highest rates of trombiculid infestation, trombiculid load, and Orientia infection in the captured rodents. Conclusions/significance: Our study provides new insights into the trombiculid fauna and prevalence of Orientia in mites collected from wild rodents in southern Chile. Orientia DNA was detected in four of the six mite species. Rates of infestation, mite loads, and Orientia prevalences differed geographically and were highest in the Aysén Region. Our data improve our knowledge on possible vectors of scrub typhus and their distribution in Chile. Publicada